Applicability of B-mode ultrasonography, ARFI elastography and contrast-enhanced ultrasound in the evaluation of chronic kidney disease in dogs - Da Cruz, Igor C.K. [UNESP]; Gasser, Beatriz [UNESP]; Maronezi, Marjury Cristina [UNESP]; Uscategui, Ricardo Andrés R.; Feliciano, Marcus Antônio R. [UNESP]; Padilha-Nakaghi, Luciana Cristina [UNESP]; Aires, Luiz Paulo N. [UNESP]; da Silva, Priscila D.A. [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this study was to verify the applicability of B-mode ultrasonography, ARFI elastography and CEUS in the diagnosis of chronic kidney disease and its Stages in dogs. 24 healthy dogs and 28 with CKD were included. In B-mode, the echogenicity, echotexture and cortico-medullary ratio of the kidneys were verified. By elastography, the shear-wave velocity of the cortical (SWVcort) and medullary (SWVmed) regions were determined and tissue deformity was evaluated. Wash-in, wash-out and peak enhancement (TPic) of the contrast in the renal parenchyma were calculated and homogeneity, presence of filling gaps and distinction of filling phases were evaluated by CEUS. Changes in echogenicity, echotexture and cortico-medullary ratio were observed only in sick patients. There was an increase in SWVcort in CKD, with a cutoff point >2.91m/s. Healthy kidneys were non-deformable and 25% had changes in gray scales. There was an increase in wash-in and TPic, changes in filling characteristics, filling failures and difficulty in distinguishing between the Stages in CEUS in CKD. It was found that dogs with CKD 2, 3 and 4 had greater SWVcort and wash-in values than CKD 1. Elastographic and CEUS changes were observed in dogs with CKD, demonstrating the applicability of ultrasonographic techniques in their diagnosis.
Keywords: ARFI; B-mode; Chronic kidney disease; Dogs; Elastography; Microbubbles; Perfusion; Renal; Stiffness; Ultrasonography; Ultrasound